فاعلية الألعاب اللغوية في علاج الأخطاء اللغوية لدى طلاب المستوى الثاني من قسم الإعداد اللغوي بجامعة الراية - Deni Rahmat Jatnika (Rayah Al-Islam, 2019)
Errors in the use of Arabic grammar is one of the problems that are often faced especially by 2nd semester students Idad al Lughawi STIBA Ar Raayah. The difference between basic structures is the biggest reason for students to make mistakes in using Arabic grammar. The method used to get the results of this study is the experimental method, which was conducted on 74 students as samples from 248 students. The results showed that the average test score for the control group on the pre-examination exam was 74.28 while the average score for the post-experimental exam was 80.57, from which the conclusion was that the test scores for the control group increased by 6,24, while the average value of the experimental group on the pre-experimental test was 76.09 while the average value of the experimental group after the experiment was 93.95, therefore the results concluded that the test scores for this group experienced a significant increase of 16, 95. Then the final conclusion after testing the hypothesis using the t-test formulates one result, namely that linguistic play has a very effective way of improving grammatical errors that occur between I’dad Lughawi Students.